Synergizing Generative Pre-Trained Transformer (GPT) Chatbots in a Process-Based Writing Paradigm to Enhance University Students’ Writing Skills - Roderick Robillos (Journal of Language and Education)
Background: The combination of the process-based writing framework and GPT-based chatbots establishes a dynamic and interactive environment, leading students through the stages of planning, drafting, revising, and editing. This collaborative approach not only elevates writing skills but also cultivates critical thinking and self-reflection, thereby transforming the writing process into a more effective and engaging learning experience. Despite the potential synergy to revolutionize the writing process, there exists a surprising lack of research within the educational domain exploring the impact of this innovative approach.